Purification and Antimicrobial Use of Egg-white Lysozyme against Staphylococcus aureus - Wang, Yuling; Xu, Xianmin; Wu, Huiting; Jia, Wenjing; Luo, Jing; Qiu, Wenqian; Huang, Jianzhong; Shu, Zhengyu (Applied Food Biotechnology, 2026)
Background and Objective: Staphylococcus aureus is a significant foodborne and zoonotic pathogen. This study aimed to enhance the anti-Staphylococcus aureus activity of egg-white lysozyme through heat treatment and synergistic combinations with natural antimicrobials. Material and Methods: The lysozyme was purified from egg white via ammonium sulfate precipitation and cation-exchange chromatography, yielding a homogeneous protein. Anti-Staphylococcus aureus activity of native lysozyme, heat-treated lysozyme and its combination with ferulic acid or Mycobacterium smegmatis acyltransferase was assessed, respectively. All experiments were carried out in triplicate and statistical analysis was carried out using SPSS software. Results and Conclusion: The specific activity of lysozyme to Micrococcus lysodeikticus was 27,407.4 U.mg-1. The lysozyme IC50 against Staphylococcus aureus was 300.8 µg.ml-1, with transmission electron microscopy verifying bacteriolytic action. Heat treatment under optimized conditions (90°C, 15 min, pH 6.2) significantly enhanced the lysozyme antibacterial activity by 35.1%, which was correlated with structural changes evidenced by circular dichroism spectroscopy. Furthermore, synergistic effects were observed when heat-treated lysozyme was combined with ferulic acid or Mycobacterium smegmatis acyltransferase (MsAcT), leading to prolonged inhibition and decreased viable bacterial counts. The findings of this research demonstrated that structural modifications and combinatorial strategies could effectively improve the efficacy and application potential of lysozyme as a natural antimicrobial agent in food safety. Keywords: Egg-white lysozyme, Ferulic acid, Heat-induced fibrillar aggregates, Mycobacterium smegmatis acyltransferase, Staphylococcus aureus Introduction Staphylococcus aureus is a Gram-positive bacterium widely spread in nature and a common foodborne pathogen. The enterotoxins (SEs) of the bacteria show significant heat resistance, rendering them difficult to completely eliminate through conventional cooking methods and posing a significant risk of food poisoning. Furthermore, S. aureus facilitates cross-infection between humans and animals via the food chain through contamination of animal feed, subsequent infection of animals and transmission to humans, establishing it as an important zoonotic pathogen. The S. aureus has been detected in various animal species and a wide range of food products, with its prevalence continuously increasing on a global scale. Therefore, S. aureus is still a high-priority target in food safety monitoring [1, 2]. To combat S. aureus contamination in food processing, diverse biological control strategies have been investigated. These include inhibition using lactic acid bacteria (LAB) probiotics [3], Lysostaphin [4], bacteriophages [5,6], essential oils (EO) [5] and lysozyme [7,8]. From these, egg-white lysozyme has widely been used due to its high catalytic activity, simple preparation and cost-effectiveness [7,9]. It inhibits S. aureus through two primary mechanisms of (1) lytic mechanism as lysozyme hydrolyzses β-1, 4-glycosidic bonds to peptidoglycan, which causes cell wall damage, induces cell lysis and results in bactericidal activity; and (2) the non-lytic mechanism, where under denaturing conditions, it suppresses growth through inherent protein characteristics such as hydrophobicity and cationic effects [8,10]. While the antimicrobial characteristics of native egg-white lysozyme are well-documented, its efficacy under common food processing conditions, particularly those involving heat, needs further investigation. Moreover, strategies to enhance its activity, especially in a heat-treated state, through combination with other natural antimicrobial agents are still under-investigation. Under various reaction conditions, the interactions between other natural antibacterial agents and egg-white lysozyme can lead to various effects on its antimicrobial activity. For example, in an alkaline solution, theaflavin covalently binds to egg-white lysozyme, resulting in significant decrease of its antibacterial activity [11]. However, in an amyloid fibril hydrogel, the interaction between epigallocatechin gallate (EGCG) and egg-white lysozyme significantly broadens the antibacterial spectrum of egg-white lysozyme [12]. Therefore, an in-depth investigation into the interaction conditions between natural antibacterial factors and egg-white lysozyme is greatly important for enhancing the antibacterial efficiency of egg-white lysozyme. This research aimed to isolate and purify egg-white lysozyme using chromatography and to assess the effect of heat treatment on its anti-S. aureus activity. Furthermore, the study prepared a synergistic combination of heat-treated lysozyme with ferulic acid and acyltransferase to develop an enhanced strategy for suppressing S. aureus growth. The experimental results demonstrated that heat-induced structural modification (fibrillar aggregation) enhanced lysozyme antimicrobial mechanism beyond native peptidoglycan hydrolysis. Moreover, it has first been reported that a synergistic combination of heat-treated lysozyme with ferulic acid and MsAcT against S. aureus significantly improves the efficacy and time of inhibition. Materials and Methods 2.1. Strains, biochemical reagents and chemical reagents Micrococcus lysodeikticus CGMCC 1.4547 and S. aureus CGMCC 1.282 were purchased from China General Microbiological Culture Collection Center, China. Bovine serum albumin (BSA) and standard protein molecular weight marker were purchased from Takara Biomedical Technology, China. Moreover, CM-Sepharose fast flow chromatography column was purchased from GE Healthcare, China. Ferulic acid, caffeic acid, gallic acid and N-acetylglucosamine (NAG) included analytical grade unless otherwise specified and purchased from Shanghai Macklin Biochemical Technology, China. 2.2. Purification of egg-white lysozyme Egg white was initially diluted by 50-fold using 50 mmol.l-1 pH8.0 tris-HCl buffer and the resulting protein solution was ultrasonicated for 10 min. The supernatant was collected by centrifugation at 12,000 rpm for 5 min at 4 °C. Solid ammonium sulfate was added to the supernatant to achieve 40% (w/v) saturation and the mixture was set to precipitate for 2 h at 4 °C. After centrifugation, the precipitate was removed and the collected supernatant was further loaded onto a CM-Sepharose fast flow column (5 × 20 cm) that was pre-equilibrated with 50 mmol.l-1 tris-HCl buffer (pH 8.5). The lysozyme was eluted with a 5-fold column volume of 50 mmol.l-1 tris-HCl buffer (pH 8.5) with increasing concentrations of NaCl (0.1 and 0.5 mol.l-1) at a flow rate of 20 ml.h-1, respectively. The active fractions were pooled. Protein concentration was assessed using Bradford method with BSA as a standard. The homogeneity of the purified egg-white lysozyme was assessed using sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE). 2.3. Activity assay of egg-white lysozyme The cell lysis activity of lysozyme from egg white to M. lysodeikticus was quantitatively assessed using spectrophotometeric assay method, which was described by the National Standard of the People's Republic of China (GB/T 30990-2014, Determination of Lysozyme Acyivity) as well as Naveed et al. [13]. Briefly, after incubation overnight, M. lysodeikticus was transferred into the fresh LB liquid media at 1% (v/v) and incubated at 37 °C for 2 h at 220 rpm. The cells were harvested by centrifugation and resuspended in 50 mmol.l-1 Na2HPO4-Na2HPO4 buffer (pH 6.2) to a final concentration of 5 × 105 CFU.ml-1. The reaction system contained 2.5 ml of cell suspension and 0.5 ml of lysozyme solution, while the control system received 0.5 ml of inactivated lysozyme solution. The reaction was carried out at 50 mmol.l-1 Na2HPO4-Na2HPO4 buffer (pH 6.2) for 5 min at 25 °C and the absorbance of the reaction system was continuously monitored at 450 nm. One unit of lysozyme activity (U) was defined as the quantity of enzyme necessary to decrease OD450 by 0.001 per minute under the standard assay condition. 2.4. Anti-Staphylococcus aureus activity of egg-white lysozyme Briefly, S. aureus in the logarithmic growth phase was used as an indicator microorganism to assess antibacterial activity of the purified lysozyme. To set the growth curve, overnight-cultured S. aureus was subcultured into the fresh LB liquid media at a 1% (v/v) inoculum and incubated at 37 °C for 14 h at 220 rpm. Samples were collected every 30 min to measure the optical density (OD) of the culture broth at 600 nm. The growth curve was plotted with OD600 on the y-axis and incubation time on the x-axis. The antibacterial assessments were carried out using a method described by Carrillo et al. [14] with slight modification. Following 2 h of subculture, S. aureus suspensions were adjusted to 5 × 105 CFU.ml-1 through serial dilution in LB liquid media. Aliquots of S. aureus suspensions were mixed with equal volumes of the purified lysozyme at various concentrations and incubated at 37 °C for 6 h at 220 rpm. The OD600 of the mixture was recorded after a 6-h subculture. The control group used 50 mmol.l-1 Na2HPO4-Na2HPO4 filter-sterilized buffer (pH 6.2) instead of lysozyme. Antibacterial activity of the purified lysozyme to S. aureus was assessed using the antibacterial ratio. Antibacterial ratio was calculated using the following equation of R = (A - B) ÷ A × 100%; in which, R was the antibacterial ratio (%); A was the OD600 value of the control group; and B was the OD600 value of the experimental group. The antibacterial effect curve was plotted with the antibacterial ratio on the y-axis and the logarithmic of the purified lysozyme concentration on the x-axis. The IC50 was defined as the purified lysozyme concentration, which resulted in a 50% decrease in the level of the antibacterial ratio, compared with untreated groups after a 6-h treatment. The IC50 value was calculated using GraphPad Prism software. The cell morphology of S. aureus after a 6-h lysozyme treatment (IC50 concentration) was reported using transmission electron microscopy (TEM). 2.5. Effects of heat treatment on anti-Staphylococcus aureus activity of the purified egg-white lysozyme To assess the anti-S. aureus effects of the heat-treated egg-white lysozyme, a specific concentration of the purified lysozyme solution was incubated at various temperatures for a set duration before assessing its anti-S. aureus activity using water bath. In this study, three key parameters were primarily investigated, including heat treatment temperature, time and initial lysozyme concentration. The temperatures were set at 37, 50, 60, 70, 80, 90 and 100 °C, respectively. The treatment times were set at 5, 10, 15, 60, 120 and 240 min, respectively. The initial lysozyme concentration were set at 601.6, 1000, 2000, 4000 and 6000 μg.ml-1, respectively. The three highlighted factors were optimized using one-factor-at-a-time method. After heat treatment, equal volumes of the lysozyme solution and S. aureus suspension were thoroughly mixed and co-cultured at 37 °C for 6 h at 220 rpm. The antibacterial ratio was then quantified. Untreated lysozyme was used as control group. To assess the effect of heat treatment on lysozyme molecular structure, circular dichroism (CD) spectroscopy was used to analyze changes in its secondary structural components before and after thermal exposure. The CD spectra were assessed using Jasco J-1500 spectropolarimeter (Jasco, Japan) with a 1-mm cell in the far-UV region from 190 to 300 nm. The concentration of lysozyme was 0.1 mg.ml-1 in 5 mmol.l-1 phosphate buffer (pH 6.2). 2.6. Inhibitory effects of phenolic acids combined with heat-treated egg-white lysozyme on Staphylococcus aureus 2.6.1. Compatibility screening of various phenolic acids with egg-white lysozyme In this experiment, the inhibitory effects of egg-white lysozyme combined with three phenolic acids (ferulic acid, caffeic acid and gallic acid) at various concentrations on S. aureus growth were assessed, respectively. The final concentrations of each phenolic acid were 200, 400, 800 and 1000 μg.ml-1, while the final concentration of egg-white lysozyme was set at 300.8 μg.ml-1. The anti-S. aureus activity analysis and antibacterial ratio calculation methods were based on those described in Section 1.4. For the control group, phenolic acids or lysozyme were replaced with 50 mmol.l-1 Na2HPO4-Na2HPO4 buffer solution (pH 6.2). 2.6.2. Effects of the heat-treated lysozyme and ferulic acid combination on Staphylococcus aureus growth The method for assessing the growth curves of S. aureus was based on Section 1.4. The heat treatment procedure for egg-white lysozyme was carried out according to Section 1.5, with the final concentration of heat-treated lysozyme adjusted to 300.8 μg.ml-1. For the control group, ferulic acid or lysozyme were substituted with 50 mmol.l-1 Na2HPO4-Na2HPO4 buffer solution (pH 6.2). 2.7. Numberized subsection inhibitory effects of Mycobacterium smegmatis acyltransferase combined with heat-treated egg-white lysozyme on Staphylococcus aureus growth The mechanism by which, M. smegmatis acyltransferase (MsAcT) combined with heat-treated egg white lysozyme inhibited the growth of S. aureus is illustrated in Fig. 6.1. The preparation of the purified MsAcT was based on the methods described by Jia et al. [15]. Briefly, recombinant Escherichia coli BL21(DE3) strain was inoculated to Luria-Bertani (LB) broth and grown at 30 °C. The IPTG was added to culture broth to the final concentration of 1 mmol.l-1, when the OD600 reached 0.6–0.8. After 14 h interval, cell pellet was collected, resuspended using loading buffer (20 mmol.l-1 pH 7.4 Na2HPO4-NaH2PO4, 20 mmol.l-1 imidazole and 500 mmol.l-1 NaCl) and then lysed using sonication. The supernatant from the cell lysate was collected and directly loaded on the HisTrap HP affinity chromatography column pre-equilibrated with loading buffer, respectively. Recombinant protein was eluted with a linear gradient of 20 ml of 20–500 mmol.l-1 imidazole in the buffer with a flow rate of 0.8 ml.min-1. The fractions with pure MsAcT were pooled and dialyzed against 20 mmol.l-1 Na2HPO4-NaH2PO4 (pH 6.2) buffer overnight at 4 ◦C. The hydrolysis activity of MsAcT to NAG was assessed according to Jiang et al. [16] and Muzzarelli and Rocchetti [17]. In brief, the reaction mixture contained 20 μg.ml-1 NAG in 20 mmol.l-1 Na2HPO4-Na2HPO4 buffer (pH 6.2). Appropriately diluted MsAcT was added into the reaction mixture to create a linear dependence of the reaction rate to protein concentration. The reaction was carried out at 37 ◦C and the kinetics was detected for 3 h at 202 nm. The specific procedure for inhibiting S. aureus growth using MsAcT combined with heat-treated egg-white lysozyme was carried out as follows: MsAcT, heat-treated egg white lysozyme and buffer solutions were sterilized using 0.22-μm filters. Then, 200 μl of appropriately diluted log-phase S. aureus cells were mixed with 200 μl of 1 mg.ml-1 MsAcT solution, while the control group received 200 μl of 50 mmol.l-1 NaH2PO4-Na2HPO4 solution (pH 6.2). After incubation at 37 °C for 3 h, 200 μl of the heat-treated egg-white lysozyme (final concentration of 300.8 μg.ml-1) were added to the experimental and control groups and mixed thoroughly, followed by incubation at 37 °C for 3 h. The samples were then centrifuged at 12,000 rpm for 3 min to separate the supernatant and the bacterial cell pellet. The protein concentration in the supernatant was measured to calculate the increase in protein, while the number of viable bacteria in the pellet was assessed according to the National Food Safety Standard of China (GB4789.2-2022, Food Microbiological Examination: Determination of Total Bacterial Count). Results and Discussion 3.1. Purification and characterization of egg-white lysozyme The purification of egg-white lysozyme was achieved through ammonium sulfate precipitation and CM-Sepharose fast flow column chromatography, resulting in 8.7-fold purification and yield of 41.0% (Table 1). Cation exchange chromatography verified particularly effective, accounting for 5.8-fold increase in specific activity. The purified enzyme was verified as homogenous using SDS-PAGE, showing a single band at 14.3 kDa (Fig. 1, Lane 6), which was similar to the molecular mass of egg-white lysozyme [18]. Its specific activity was assessed as 27,407.4 U.mg-1 using M. lysodeikticus cells as substrate. This value was less than that reported by Chen et al. [18], a discrepancy likely attributable to the use of whole cells in this assay instead of the isolated cell walls used in the highlighted study. A gradual loss of total activity was observed throughout purification. Particularly, lysozyme was detected in pellets at a relatively low ammonium sulfate saturation (40%), suggesting the potential formation of insoluble aggregates under these conditions, as previously documented [19, 20]. For practical uses, it is critical to state that the growth state of M. lysodeikticus, affected by culture conditions and equipment, significantly affects the assessed specific activity [11, 13, 21]. Therefore, standardizing the substrate by setting the growth curve and harvesting log-phase cells under local laboratory conditions is essential for accurate activity assessment. In this study, the buffer solution for the assessment of the egg-white lysozyme activity according to the National Standard of the People's Republic of China (GB/T 30990-2014) requirements included 50 mmol.l-1 Na2HPO4-NaH2PO4 buffer (pH 6.2). In practical fields, particularly in the food processing industry, buffer solutions with pH 6.2 are rarely used. Therefore, it is essential to assess optimal pH and temperature under the specific conditions necessary for the target uses, when assessing using effectiveness of egg-white lysozyme. 3.2. Anti-Staphylococcus aureus activity and mechanism of the purified egg-white lysozyme The growth curve of S. aureus was characterized, identifying a log phase from 1 to 8 h (Fig. 2A), similar to the previous reports [22]. Cells from the exponential phase (2 h) were used for the assays. The IC50 of native lysozyme against S. aureus was 300.8 μg.ml-1 (Fig. 2B). The antibacterial efficacy of lysozyme is affected by the composition and sequence of bacterial cell wall peptidoglycan, as well as the physiological state of the enzyme [23, 24]. Lysozyme fights microbes through bacteriostatic, bactericidal and bacteriolytic mechanisms [25]. The transmission electron microscopy (TEM) images provided direct evidence of the bacteriolytic action, showing damaged S. aureus cell walls with distinct light/dark contrast and the collapse of cells, leading to leakage of intracellular contents (Fig. 2C, arrows). Despite this significant effect, the inhibitory activity of the native lysozyme is difficult to sustain over extended times (Figs. 2A, 5A), highlighting a limitation for its use as a standalone antimicrobial agent. 3.3. Enhancement of anti-Staphylococcus aureus activity using heat treatment and structural changes Heat treatment under optimized conditions (600 μg.ml-1, 90°C, 15 min, pH 6.2) enhanced the anti-S. aureus activity of lysozyme by 35.1%, achieving 82.5% inhibition compared to the native enzyme (Fig. 3A–C). This increase in activity after thermal denaturation was similar to that against other microbes such as SARS-CoV-2 and Bacillus subtilis [26, 27, 28]. Structural analysis revealed the reason behind this enhancement as a significant rearrangement of secondary structure occurred, with α-helix content decreasing from 35.59 to 23.60% and β-sheet, β-turn and random coil structures increasing (Fig. 3D, Table 2). This unfolding and proliferation of β-sheets drived the formation of fibrillar aggregates [30,29], which were postulated to perforate microbial membranes, a mechanism distinct from the native enzyme peptidoglycan hydrolysis [27]. This suggested that structural modification wa a viable strategy to improve the efficacy of lysozyme. 3.4. Synergistic anti-Staphylococcus aureus effects of heat-treated egg-white lysozyme and phenolic acids From the phenolic acids (ferulic, caffeic and gallic acids), ferulic acid showed the highest inhibition (52.2%) at 200 μg.ml-1, though differences diminished at higher concentrations (1000 μg.ml-1), where all acids reached ~99% inhibition (Fig. 4A–C). Ferulic acid is reported to inhibit S. aureus by suppressing tetK and MsrA efflux pumps on the bacterial membrane [31,32]. A combination of 400 μg.ml-1 ferulic acid with native lysozyme (300.8 μg.ml-1) showed a synergistic effect, increasing inhibition by respectively 12.3 and 29%, compared to either compound alone (Fig. 4A). This synergy was further increased, when ferulic acid was combined with heat-treated lysozyme, reducing bacterial biomass (OD600) by additional 18.7%, compared to the combination with native enzyme (Fig. 5A). The optimal protocol involved sequential addition of heat-treated lysozyme added at time zero, followed by ferulic acid after 6 h. This not only delayed the entry into the log phase by an additional hour but also decreased final biomass by 48.8% (Fig. 5B). This demonstrated that combining lysozyme with other antibacterial compounds, particularly after structural modification, could significantly enhance and prolong its inhibitory effect, potentially broadening its antibacterial spectrum [12,33]. However, when designing such combinations, concentration and addition sequence of egg-white lysozyme and phenolic acid, biocompatibility, reaction condition and differences in the mechanisms of action must carefully be addressed. Otherwise, adverse effects may occur. For example, in a solution with pH 9.0, phenolic acids (e.g., theaflavin) form covalent bonds with egg-white lysozyme, resulting in a 20% decrease in the antibacterial activity of egg-white lysozyme [12,33]. 3.5. Synergistic inhibition using MsAcT and heat-treated lysozyme The enzyme MsAcT hydrolyzes acyl groups on peptidoglycan structural units, theoretically facilitating subsequent hydrolysis by lysozyme (Fig. 6A). Experimental data verified this synergy. Treatment with heat-treated lysozyme alone increased the extracellular protein concentration by 0.115 mg.ml-1, indicating cell lysis. When combined with MsAcT, the protein release increased further substantially by 0.208 mg.ml-1 (Fig. 6B). This was verified by colony counts, which showed a decrease in viable cells from 1.69 × 108 CFU.ml-1 (lysozyme alone) to 1.41 × 108 CFU.ml-1 (combination treatment) (Fig. 6C). This is a significant finding, as bacterial deacylation of peptidoglycan is typically a resistance mechanism that decreases hydrophobic interaction with lysozyme [10]. However, the present results demonstrated that external enzymatic deacylation by MsAcT could instead sensitize cells to lysozyme. It is challenging to explain this novel result at the molecular level. Since the lysozyme used in this research was achieved through separation and purification from egg-white and its 3-dimensional (3D) structure has not been resolved, molecular docking techniques cannot be used to investigate the differential interactions between NAM/NAG and deacetylated NAM/NAG with the lysozyme. Additionally, MsAcT is a promiscuous biocatalyst possessing multiple catalytic activities such as hydrolytic activity and perhydrolysis activity [15]. Further in-depth investigation is needed to assess which catalytic activity dominates during its synergistic action with egg-white lysozyme in inhibiting S. aureus. When egg-white lysozyme acts synergistically with other natural antibacterial agents to inhibit the growth of S. aureus, biocompatibility is one of the primary key parameters. Environmental conditions such as buffer pH [10,24], ionic strength [10,20,24] and temperature [14,27] of the egg-white lysozyme solution can alter its conformational state to various degrees; thereby, decreasing its antibacterial activity. Polyphenolic compounds may modify and disrupt the conformation of egg-white lysozyme, diminishing or eliminating its antibacterial activity [11, 12, 21, 31]. When other antibacterial proteins (e.g., proteases) act synergistically with egg-white lysozyme to inhibit the growth of S. aureus, the degradation of lysozyme by proteases can directly lead to its inactivation [14]. This study investigated the synergistic inhibitory effect of egg-white lysozyme and ferulic acid on growth of S. aureus under a sequential interaction mechanism, where two antibacterial agents were sequentially added to the reaction system to inhibit the bacterial growth. The experimental results indicated that the sequential interaction mechanism could partially overcome the issue of biocompatibility and maximize the antibacterial efficacy [Fig. 5B]. With the public in-depth understanding of the bacterial resistance mechanisms, growing awareness of environmental hazards caused by antibiotic misuse and heightened self-health consciousness, prohibition of antibiotics in animal feed and breeding processes has become a global interest. Therefore, it is vital to actively search for various alternatives to antibiotics [34, 35, 36]. From various antibiotic alternatives, egg-white lysozyme is a promising candidate due to its excellent biosafety. This study demonstrated that structural modification through heat treatment and strategic combination with other antimicrobials such as ferulic acid or enzymes such as MsAcT could significantly enhance its efficacy and time of action against S. aureus. Further studies should focus on clarifying the detailed mechanisms of these synergistic interactions and investigating other modification strategies such as glycosylation and lipophilization [10,24] to fully realize the potential of lysozyme as an effective antibiotic alternative. Conclusion In conclusion, this study successfully purified and characterized egg-white lysozyme and demonstrated that its anti-S. aureus activity could significantly be enhanced through thermal denaturation and synergistic combinations. Heat treatment induced structural reorganization of lysozyme, increasing its β-sheet content and enabling membrane-perforating antibacterial mechanisms distinct from its native lytic activity. Furthermore, combining heat-treated lysozyme with ferulic acid or MsAcT resulted in the synergistic effects, delaying bacterial growth and improving bacteriolytic efficacy. The results highlighted the potential of modified lysozyme as part of integrated natural preservation systems to improve food safety. Further studies should focus on explaining detailed mechanisms of synergy and investigating other modification methods to further broaden the applicability and effectiveness of lysozyme-based antimicrobial interventions. To better promote this process in the field of food processing, follow-up research should thoroughly investigate its use effects, affecting factors and long-term stability in real food matrices (e.g., meat and dairy products). Additionally, a comparison of production costs and profitability with other antibacterial processes is necessary. Acknowledgements This research was supported financially by the National Natural Science Foundation of China (nos. 31370802 and 31870787) and Fujian Province Natural Science Foundation (no. 2021J01169). Declaration of competing interest The authors declare no conflict of interest. Authors’ Contributions Conceptualization, W.H. and X.X.; methodology, W.H.; software, Q.W.; validation, L.J., .J.W. and Q.W.; formal analysis, W.H. and S.Z.; investigation, X.X.; resources, J.W.; data curation, L.J.; writing—original draft preparation, W.Y.; writing—review and editing, S.Z.; supervision, S.Z.; project administration, H.J.; funding acquisition, S.Z. Using Artificial Intelligent Chatbots No artificial intelligent chatbots have been used in sections of this manuscript. Ethical Consideration The subjects of this study are egg white lysozyme and Staphylococcus aureus. As no animal or human trials are involved, no ethical review documentation is required.